2009
DOI: 10.1111/j.1439-0396.2008.00826.x
|View full text |Cite
|
Sign up to set email alerts
|

Fish protein substrates can substitute effectively for poultry by‐product meal when incorporated in high‐quality senior dog diets

Abstract: An experiment was conducted to analytically define several novel fish substrates and determine the effects of feeding diets containing these substrates on total tract nutrient digestibilities and on immune status of senior dogs. The control diet contained poultry by-product meal while test diets contained 20% milt meal (MM), pink salmon hydrolysate (PSH) and white fish meal (WFM) added at the expense of poultry by-product meal. Concentrations of lymphocytes positive for CD3, CD4, CD8 and CD21 cell-surface mark… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…Fish meal (FM) carries large quantities of energy per unit weight and is a source of high‐quality protein and highly digestible essential amino and fatty acids (Zinn et al., 2009). Numerous studies have shown that fish meal generally improves the growth and performance of starter and grower pigs (Kjeldsen et al., 1981; de Moura and Fowler, 1983; Newport and Keal, 1983; Pike et al., 1984).…”
Section: Introductionmentioning
confidence: 99%
“…Fish meal (FM) carries large quantities of energy per unit weight and is a source of high‐quality protein and highly digestible essential amino and fatty acids (Zinn et al., 2009). Numerous studies have shown that fish meal generally improves the growth and performance of starter and grower pigs (Kjeldsen et al., 1981; de Moura and Fowler, 1983; Newport and Keal, 1983; Pike et al., 1984).…”
Section: Introductionmentioning
confidence: 99%
“…() reported an apparent ileal digestibility of CP of 80.4% and 82.8% in dogs fed extruded diets containing fresh beef or fresh poultry as protein sources respectively, but digestibility of the protein ingredients or diets prior to extrusion was not reported. Reports focusing on animal protein hydrolysates as protein sources in extruded dog foods have, to our knowledge, reported only ATTD of CP in dogs, and the effects of extrusion were not addressed (Verlinden et al., ; Zinn et al., ). The results of the present study therefore warrant further, more controlled, studies focusing on the effects of extrusion processing on CP and AA digestibility of raw animal protein sources and animal protein hydrolysates incorporated into extruded dog foods.…”
Section: Discussionmentioning
confidence: 99%
“…The most important of which are: White fish powder: You get it by drying and grinding for Whitefish or whitefish offal. Its properties: it has a high content of lysine -methionine -tryptophan and contains a high percentage of mineral salts, where it contains 8% of calcium and 3.5% of phosphorus and contains a percentage of micro -mineral elements (manganese -iron -iodine) and is a good source of B vitamins (B12riboflavin-choline) [70]. Herring fish powder: It contains about 70% raw protein, it is recommended to add them in specific proportions of 2-5% in order to increase their prices, and it is also recommended not to add them at the end of the fattening period or in egg production relations due to the transfer of the smell of fish in the carcass and eggs [71].…”
Section: (Iii) Sources Of Animal Proteinsmentioning
confidence: 99%